Coastal landscapes and environment. Fishing communities in greater Resistencia, Argentina - Coccato, Marcelo Andrés (2016)
Fil: Coccato, Marcelo Andrés. Universidad Nacional del Nordeste. Facultad de Arquitectura y Urbanismo; Argentina.